Role of the Corpus Callosum in Functional Connectivity - Quigley, Michelle; Cordes, Dietmar; Turski, Pat; Moritz, Chad; Haughton, Victor; Seth, Raj; Meyerand, M. Elizabeth (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Regional cerebral blood flow fluctuates synchronously in corresponding brain regions between the hemispheres. This synchrony implies neuronal connections between brain regions. The synchrony of blood flow changes is defined operationally as functional connectivity. Our purpose was to measure functional connectivity in patients with corpus callosal agenesis, in whom the interhemispheric connectivity is hypothetically diminished.METHODS: In three patients with agenesis of the corpus callosum, functional MR imaging was performed while patients performed text-listening and finger-tapping tasks. Functional images were also acquired while the patients performed no specific task (resting state). Regions of activation temporally correlated with the performance of the tasks were identified by cross-correlating the task data with a reference function. Voxel clusters (seed voxels) that corresponded to regions of activation in the task-activation data set were selected in the resting data set. All the voxels in the resting 3D data set that had a correlation coefficient exceeding 0.4 were identified. The number of these voxels in the ipsilateral and contralateral hemispheres was tabulated.RESULTS: In all patients, technically adequate functional MR and functional connectivity MR maps were obtained. For both tasks, activation was found in both hemispheres. For all of the seed voxels, significantly more functionally connected voxels were found in the ipsilateral hemisphere than in the contralateral hemisphere. For most seed voxels, no functionally connected voxels were found in the contralateral hemisphere.CONCLUSION: Interhemispheric functional connectivity in the motor and auditory cortices is diminished in patients with agenesis of the corpus callosum compared with that of healthy subjects.